Sigma-1 receptor deficiency reduces MPTP-induced parkinsonism and death of dopaminergic neurons - Hong, J (Cell Death Dis, 2015)
Sigma-1 receptor (σ(1)R) has been reported to be decreased in nigrostriatal motor system of Parkinson's disease patients. Using heterozygous and homozygous σ(1)R knockout (σ(1)R(+/−) and σ(1)R(−/−)) mice, we investigated the influence of σ(1)R deficiency on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-impaired nigrostriatal motor system. The injection of MPTP for 5 weeks in wild-type mice (MPTP-WT mice), but not in σ(1)R(+/−) or σ(1)R(−/−) mice (MPTP-σ(1)R(+/−) or MPTP-σ(1)R(−/−) mice), caused motor deficits and ~40% death of dopaminergic neurons in substantia nigra pars compacta with an elevation of N-methyl-d-aspartate receptor (NMDAr) NR2B phosphorylation. The σ(1)R antagonist NE100 or the NR2B inhibitor Ro25-6981 could alleviate the motor deficits and the death of dopaminergic neurons in MPTP-WT mice. By contrast, MPTP-σ(1)R(+/−) mice treated with the σ(1)R agonist PRE084 or MPTP-σ(1)R(−/−) mice treated with the NMDAr agonist NMDA appeared to have similar motor deficits and loss of dopaminergic neurons as MPTP-WT mice. The pharmacological or genetic inactivation of σ(1)R suppressed the expression of dopamine transporter (DAT) in substantia nigra, which was corrected by NMDA. The activation of σ(1)R by PRE084 enhanced the DAT expression in WT mice or σ(1)R(+/−) mice. By contrast, the level of vesicular monoamine transporter 2 (VMAT2) in σ(1)R(+/−) mice or σ(1)R(−/−) mice had no difference from WT mice. Interestingly, MPTP-WT mice showed the reduction in the levels of DAT and VMAT2, but MPTP-σ(1)R(−/−) mice did not. The inactivation of σ(1)R by NE100 could prevent the reduction of VMAT2 in MPTP-WT mice. In addition, the activation of microglia cells in substantia nigra was equally enhanced in MPTP-WT mice and MPTP-σ(1)R(−/−) mice. The number of activated astrocytes in MPTP-σ(1)R(−/−) mice was less than that in MPTP-WT mice. The findings indicate that the σ(1)R deficiency through suppressing NMDAr function and DAT expression can reduce MPTP-induced death of dopaminergic neurons and parkinsonism.